L'enseignant face à la difficulté de la classe : Capacité à agir et décrochage enseignant. - Séraphin Alava (Université de Provence, 2016)
Within a teacher's professional practice, it is often that he/she will handle stressful situations, being both difficult and tiring. Teacher's ability to handle these situations is at the heart of research on teacher action since the early nineties. In several circumstances, these situations can disturb the professionals and have a significant impact on their health and behavior. In such cases, the teacher can either just drop out of the situation or develop feelings and behaviors showing its inability to act (disempowerment). As part of a study on the modalities of teacher management of school dropout situations conducted among 640 teachers from Midi-Pyrénées (France), we identified and validated a scale for assessing teacher attrition and we showed the links between this scale of attrition practices and the general level of fatigue, stress and discomfort experienced by the teacher.